MATHEMATICAL MODELLING OF FACTORS OF INVESTMENT ATTRACTIVENESS OF REGIONAL LANDS - Radzinska, Yu.; Bahin, М.; Goi, V.; Frolov, V. (Municipal economy of cities. Series: «Economy science», 2024)
The transformations in land relations at the regional level and the growth of crisis phenomena regarding land use require a rethinking of approaches to ensure land investment attractiveness. In the modern context, land resources at the regional level are one of the main components that influence the processes of reforming local self-government and creating conditions for forming the basis for territorial development. In addition, attracting domestic and foreign investments and ensuring the efficiency of land use are becoming vital to improving the investment attractiveness of land. Moreover, to implement this process, it is necessary to create a quantitative basis for decision-making and secure investment attractiveness based on mathematical modelling. The study reached the goal of determining the directions and features of mathematical modelling of investment attractiveness factors of regional lands. At the same time, it has achieved the following objectives: to characterise the method of mathematical modelling; to present the results of the application of mathematical modelling of factors of the investment attractiveness of the lands of the regions. As a result of mathematical modelling, we established cause-and-effect relationships between systemic factors and the integral indicator of the level of investment attractiveness of the lands of the regions. It made it possible to form a quantitative basis for forecasting changes in the integral indicator and to develop measures to increase the level of investment attractiveness of land, accounting for the peculiarities of the formation and use of spatial, economic, urban planning, environmental, innovative, security, and legal support. Processes of mathematical modelling of investment attractiveness factors of regional lands based on correlation-regression analysis and model adequacy criteria, which, in contrast to the existing ones, allowed for establishing cause-and-effect relationships between indicators of investment attractiveness, gained further development.